346. CUTOFF VALUE OF THORACOABDOMINAL PRESSURE GRADIENT FOR GASTROESOPHAGEAL REFLUX DISEASE ON STARLET HIGH-RESOLUTION MANOMETRY. (24th September 2022) - Masuda, Takahiro; Tsuboi, Kazuto; Hoshino, Masato; Yamamoto, SeRyung; Akimoto, Shunsuke; Tanishima, Yuichiro; Uno, Kohei; Hara, Keigo; Takahashi, Keita; Sakashita, Yuki; Fukushima, Naoko; Takeuchi, Hideyuki; et al.
Abstract: Derangement of thoracoabdominal pressure gradient (TAPG) associates with gastroesophageal reflux disease (GERD). High-resolution esophageal manometry (HRM) is the gold standard to assess pathophysiology of GERD. Starlet HRM is widely used in Japan; however, TAPG values on Starlet HRM system have been unstudied. The aim of this study is to propose the cutoff value of TAPG to discriminate GERD on Starlet HRM system. We included patients who underwent both Starlet HRM and 24-hour multichannel intraluminal impedance pH study (MII-pH) at our hospital between July 2018 and February 2022. Patients were divided into 3 groups; control group (both HRM and MII-pH were within normal limits), GERD group (acid exposure time [AET] ≥4.0% and/or DeMeester score ≥ 14.72), and non-pathological reflux group. Normal MII-pH values were defined according to our previous study using healthy Japanese volunteers (Yano, et al. Esophagus, 2017); AET <2.5%, DeMeester score < 11, and liquid reflux episodes <80.0. TAPG and adjusted TAPG were analyzed (shown in Figure). Total 102 patients met the study criteria (mean age 53.0 ± 16.0 years, 32 females). Thirty-four patients were categorized into the control group, 31 patients were into the GERD group, and 37 patients were into the non-pathological reflux group. In the control group, 5th and 95th percentiles of TAPG were − 3.4 and 24.3 mmHg, and those of adjusted TAPG were − 50.7 and 1.6 mmHg. TAPG poorly correlated with acid exposure time (AET) (rs = 0.287, p = 0.003); however, adjusted TAPG well-correlated with AET (rs = 0.505, p < 0.001). ROC analysis showed that the estimated cutoff of adjusted TAPG was −11.1 mmHg (sensitivity 71.0%, specificity 71.8%, AUC 0.742, p < 0.001). Adjusted TAPG is associated with antireflux competency across the esophagogastric junction. Estimated cutoff value of adjusted TAPG was −11.1 mmHg in the study cohort. Further study is warrantied.